Therapeutic hypothermia versus normothermia in adult patients with traumatic brain injury: a meta-analysis - Zhu, Youfeng (Springerplus, 2016)
INTRODUCTION: Many single-center studies and meta-analyses demonstrate that therapeutic hypothermia (TH), in which the body temperature is maintained at 32–35°C, exerts significant neuroprotection and attenuates secondary intracranial hypertension after traumatic brain injury (TBI). In 2015, two well-designed multi-center, randomized controlled trials were published that did not show favorable outcomes with the use of TH in adult patients with TBI compared to normothermia treatment (NT). Therefore, we performed an updated meta-analysis to assess the effect of TH in adult patients with TBI. METHODS: We reviewed the PubMed, EMbase, Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, and Wanfang Databases. We included randomized controlled trials that compared TH and NT in adult patients with TBI. Two reviewers assessed the quality of each study and independently collected the data. We performed the meta-analysis using the Cochrane Collaboration’s RevMan 5.3 software. RESULTS: We included 18 trials involving 2177 patients with TBI. There was no significant heterogeneity among the studies. TH could not decrease mortality at 3 months post-TBI (RR 0.95; 95 % CI 0.59, 1.55; z = 0.19, P = 0.85) or 6 months post-TBI (RR 0.96; 95 % CI 0.76, 1.23; z = 0.29, P = 0.77). There were no significant differences in unfavorable clinical outcomes when TH was compared to NT at 3 months post-TBI (RR 0.79; 95 % CI 0.56, 1.12; z = 1.31, P = 0.19) or 6 months post-TBI (RR 0.80; 95 % CI 0.63, 1.00; z = 1.92, P = 0.05). TH was associated with a significant increase in pneumonia (RR 1.51; 95 % CI 1.12, 2.03; z = 2.72, P = 0.006) and cardiovascular complications (RR 1.75; 95% CI 1.14, 2.70; z = 2.54, P = 0.01). CONCLUSIONS: Therapeutic hypothermia failed to demonstrate a decrease in mortality and unfavorable clinical outcomes at 3 or 6 months post-TBI. Additionally, TH might increase the risk of developing pneumonia and cardiovascular complications.